2022
DOI: 10.3389/fnint.2022.827518
|View full text |Cite
|
Sign up to set email alerts
|

Monophasic-Quadripulse Theta Burst Magnetic Stimulation for Motor Palsy Functional Evaluation After Intracerebral Hemorrhage

Abstract: Transcranial magnetic stimulation (TMS) is commonly employed for diagnostic and therapeutic purposes to enhance recovery following brain injury, such as stroke or intracerebral hemorrhage (ICH). Single-pulse TMS, most commonly used for diagnostic purposes and with motor evoked potential (MEP) recordings, is not suitable for clinical use in patients with severe motor paresis. To overcome this problem, we developed a quadripulse theta burst transcranial magnetic stimulation (QTS) device that combines the output … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…These correlations were higher for amplitude than for RMTs, and linear correlations were observed for mylohyoid-MEPs after QBS5 alone. Although these correlations were relatively weak, they are clearly compatible with previous QTS results for FDI-MEPs ( Fujiki et al, 2022 ). Mylohyoid MEP facilitations after QBS5 conditioning and QTS amplification for FDI MEP relies on fundamentally different neuromodulations, this supports the hypothesis that presynaptic projections to pyramidal cells in the swallowing-related hyoid muscle group are less frequent than in the hand muscles and therefore less accessible to transsynaptic stimulation ( Guggisberg et al, 2001 ).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…These correlations were higher for amplitude than for RMTs, and linear correlations were observed for mylohyoid-MEPs after QBS5 alone. Although these correlations were relatively weak, they are clearly compatible with previous QTS results for FDI-MEPs ( Fujiki et al, 2022 ). Mylohyoid MEP facilitations after QBS5 conditioning and QTS amplification for FDI MEP relies on fundamentally different neuromodulations, this supports the hypothesis that presynaptic projections to pyramidal cells in the swallowing-related hyoid muscle group are less frequent than in the hand muscles and therefore less accessible to transsynaptic stimulation ( Guggisberg et al, 2001 ).…”
Section: Discussionsupporting
confidence: 91%
“…We analyzed data from the same 65 participants included in our previous study, which demonstrated the superiority of monophasic quadripulse theta-burst magnetic stimulation (QTS) in patients with hand motor paralysis following left hemisphere intracerebral hemorrhage (ICH) ( Fujiki et al, 2022 ). The original study included a control group of 10 healthy, right-handed men (age range: 40–68 years; mean ± SD: 58.5 ± 10.8 years) without any contraindications to TMS, as well as 65 patients with hypertension who had experienced putaminal ICH (5 women, 60 men; age range: 55–80 years; mean ± SD: 68.9 ± 11.8 years).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations